Hambatan Dakwah Di Masjid Taqwa Sikilang Kecamatan Sungai Aur Kabupaten Pasaman Barat - Wahilul Wahdi; Penmardianto Penmardianto (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
The mosque is a place of worship for Muslims who have a strategic role for the advancement of Islamic civilization. Islam is a religion of da'wah, namely a religion that calls on or assigns its people to spread and broadcast Islam to all mankind in all corners of the world as rahmatan lil alamin. Islamic teachings and messages should be disseminated to mankind throughout the world by way of preaching. The purpose of this study was to find out the obstacles to da'wah that occurred at the Taqwa Sikilang Mosque, Sungai Aur District, West Pasaman Regency. This type of research is a type of qualitative approach that is descriptive, namely collecting data by means of observation, interviews and documentation. The results of this study indicate that the obstacles to preaching at the Taqwa Sikilang Mosque, Sungai Aur District, West Pasaman Regency are: the difficulty of inviting religious teachers to Sikilang jorong because the distance is so far.